Winter wheat response to nitrogen rate and management across Kansas environments - Leiva Rivarola, Julio Cesar (My University, 2026)
Nitrogen (N) fertilizer management is one of the primary factors driving winter wheat (Triticum aestivum L.) productivity, profitability, and grain quality in Kansas; however, agroclimatic variability across the state represents a consistent challenge for optimizing fertilizer use. This research evaluated winter wheat response to N fertilization across ten site-years during the 2023-2024 and 2024-2025 growing seasons. The first study evaluated grain yield and grain protein concentration responses to increasing N rates (0 to 202 kg N ha-1) to characterize environmental variability and determine site-specific agronomic optimum N rate (ANOR). The second study evaluated the effectiveness of diverse management strategies, varying in N source, timing, placement, and inhibitor use, applied at a constant N rate of 67 kg N ha-1, using the site-specific expected responses from the first study as a baseline to compare management effects. Results from the first study indicated that grain yield response was highly variable, with AONR ranging from 116 to 185 kg N ha-1 across responsive environments. Environments with limited seasonal precipitation or high initial residual soil N exhibited weak or no grain yield response, whereas grain protein concentration increased consistently across all site-years, often continuing to increase after grain yield had plateaued. In the second study, alternative management strategies did not consistently improve grain yield relative to the expected baseline; instead, environmental conditions were the primary determinants of grain yield at a constant N rate. However, nitrogen management more frequently influenced grain protein concentration and apparent recovery efficiency (ARE). Strategies that delayed or split N application, such as split-applied UAN, often increased grain protein, while fall or early spring applications tended to result in lower protein responses. These findings demonstrate that the effectiveness of both N rate and management practices is defined by site-year conditions, including precipitation patterns and soil N supply. This research highlights the necessity of site-specific management, suggesting that producers must balance N rate and timing decisions based on local environmental conditions, grain yield potential, and specific goals for grain yield versus grain quality.
Keywords: Winter wheat; Nitrogen management; Nitrogen use efficiency; Winter wheat grain yield; Winter wheat grain protein; Nitrogen fertilizer